Językowy świat małych ojczyzn czyli słowiańskie pogranicza językowe - Tokarz, Emil (Slavia Centralis, 2020)
Linguistic world of small homelands: Borderlines of Slavic Languages The world of small homelands, lands which are lost in the sea of different and sometimes unfriendly civilizations and cultures, has resolutely defended its identity, its native language and religion. Living on the language borderlines, the Slavic people have put effort into organizing themselves by trying to sustain their identity through incorporating the new values into the native traditions. The Slavic tradition has been the source of inspiration to new challenges in the contemporary world for many of them.